Performance of a Multidisciplinary Pancreatic Cancer Conference in Predicting and Managing Resectable Pancreatic Cancer. Issue 1 (January 2019) - Rao, Bharat; Syed, Aslam; Singh, Shailendra; Gulati, Abhishek; Moussiade, Ghita; Garg, Mrinal; Sharma, Manav; Morrissey, Suzanne; Williams, Harry; Atkinson, Donald; Schiffman, Suzanne; Monga, Dulabh; et al.
Abstract : Objectives: Surgery is the curative treatment for pancreatic ductal adenocarcinoma (PDA). Guidelines recommend utilizing a multidisciplinary pancreatic cancer conference (MDPC) in treatment; however, data are limited. The objective of this study was to assess the accuracy of an MDPC. Methods: Patients with PDA presented at an MDPC were prospectively collected from April 2013 to August 2016. Patients were included if the MDPC predicted them to have resectable PDA and underwent upfront surgery. Secondary aims were to compare differences in tumor characteristics, time to surgery, and resection rates with patients prior to MDPC implementation (pre-MDPC). Results: A total of 278 patients were presented at the MDPC. After excluding borderline and nonresectable cases, 91 patients were predicted as resectable on evaluation, and 70 were fit for surgery. The MDPC predicted resection in 91.4%. The MDPC had larger tumor size (32.6 vs 24.0 mm), greater proportion of stage II tumor, and a shorter time from diagnosis to resection (27.3 vs 35.5 days) compared with the pre-MDPC. Microscopically negative resections were similar between MDPC and pre-MDPC (85.9% vs 88.0%) despite advanced tumor size and stage. Conclusions: The MDPC demonstrates a high resection rate. Compared with a pre-MDPC, MDPC provides shorter time to surgery and selects for advanced tumors.